Statistical Thinking: Problems of Definition and Formation - M. V. Karmanov (Статистика и экономика, 2025)
The purpose of the article is to attract the attention of professional environment to the problems of statistical thinking formation in Russia. Unfortunately, at present there is not yet a clear understanding of the scientific definition of “statistical thinking”, which brings notable difficulties in the process of developing a mechanism and taking into account the peculiarities of the formation of statistical thinking in society, especially among young rising generations. The paper concludes that in the existing circumstances it is extremely important to consolidate the efforts of the statistical community aimed at concretizing the content of statistical thinking and solving the problems related to the extended reproduction of its direct carriers.